2022
DOI: 10.1111/tpj.15742
|View full text |Cite
|
Sign up to set email alerts
|

SEC1A is a major Arabidopsis Sec1/Munc18 gene in vesicle trafficking during pollen tube tip growth

Abstract: SUMMARY Pollen tubes (PTs) grow by the targeted secretion of new cell wall material to their expanding tip region. Sec1/Munc18 (SM) proteins promote membrane fusion through regulation of the SNARE complex. We have previously shown that disruption of protein glycosylation in the Arabidopsis thaliana hpat1 hpat3 double mutant leads to PT growth defects that can be suppressed by reducing secretion. Here, we identified five point mutant alleles of the SM protein SEC1A as hpat1/3 suppressors. The suppressors increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 68 publications
3
9
0
Order By: Relevance
“…plc6-4 also decreased pollen germination, as does plc6-2 and plc6-3 (in the hpat1/3 background), consistent with a role of PLC6 in promoting secretion. Because these phenotypes are similar to what we previously observed in the hpat1/3;exo70a2-2 and other secretion mutant suppressors (Beuder et al, 2020, 2022), and PLCs are known to regulate PI(4,5)P 2 availability at the plasma membrane, we reasoned that PLC6 may influence secretion by regulating exocyst binding site availability and affecting apical secretion; however, there are important phenotypic differences to note between the plc6-4 and the other known hpat1/3 suppressor mutations.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…plc6-4 also decreased pollen germination, as does plc6-2 and plc6-3 (in the hpat1/3 background), consistent with a role of PLC6 in promoting secretion. Because these phenotypes are similar to what we previously observed in the hpat1/3;exo70a2-2 and other secretion mutant suppressors (Beuder et al, 2020, 2022), and PLCs are known to regulate PI(4,5)P 2 availability at the plasma membrane, we reasoned that PLC6 may influence secretion by regulating exocyst binding site availability and affecting apical secretion; however, there are important phenotypic differences to note between the plc6-4 and the other known hpat1/3 suppressor mutations.…”
Section: Discussionsupporting
confidence: 89%
“…The GF(EXT3)P reporter is Hyp O- arabinosylated in an HPAT-dependent manner; therefore, our data suggested that Hyp O- arabinosylation may regulate the rate of EXO70A2-mediated extensin secretion. We also observed that loss of function mutations in SEC15A suppressed hpat1/3 PT growth defects (Beuder et al, 2022). Sec15 is another member of the exocyst complex and is required for PT germination, growth, and fertility (Hála et al, 2008).…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations